Investigating the Usability, Efficacy and Accuracy of a Medication Entering Software System for a Healthcare Robot - Martini, Nataly; Broadbent, Elizabeth; Koo, Jasmine; Lam, Laurence; Verches, Diane; Zeng, Sophie; Montgomery-Walsh, Rhea; Sutherland, Craig (Frontiers in Robotics and AI, 2022)
Purpose: This research aimed to evaluate medication software for a healthcare robot. Study I compared two software versions (RoboGen and RoboGen2) for system usability, speed and accuracy of medication entry; Study II evaluated system usability and community pharmacists’ views of RoboGen2. Methods: Study I had a within-subjects experimental design and recruited 40 Health Sciences students to enter different, comparable sets of prescriptions into the two systems, in randomized order, within a limit of 15 minutes. Screen activity was recorded to observe prescription errors. Study II had a cross-sectional observational design and recruited 20 community pharmacists using convenience sampling. Pharmacists entered three prescriptions using RoboGen2. Participants in both studies completed the System Usability Scale (SUS) following each task. Study I participants completed a questionnaire on system preference, and Study II participants a semi-structured interview. Results: Study I participants preferred Robogen2 (p<0.001) due to its sleek and modern layout, good flow, ease of use, and intuitive design. SUS scores (t(40)= -3.40, p=0.002) and speed of medication entry favored Robogen2 (t=3.65, p <0.001). No significance was found in accuracy (t=1.12, p=0.27). In study 2, pharmacists rated the usability of RoboGen2 below average. Themes from interviews were navigation and streamlining the system, ease of use, and integration with pharmacy software systems. Conclusion: Adding safety features and better aesthetics can improve the usability and safety of a medication prescription system. Streamlining workflow and pre-populating data can increase speed of prescription entry without compromising patient safety. However, a better approach is integration with pre-existing pharmacy systems to reduce workload while incorporating safety features built into existing dispensing systems.